A Comparison of the Antioxidant Effects Between Hydrogen Gas Inhalation and Vitamin C Supplementation in Response to a 60-Min Treadmill Exercise in Rat Gastrocnemius Muscle - Chaoqun, Li; Yuqi, Zhao; Shi, Zhou; Zhenghui, Yu; Li, Wen (Frontiers in Physiology, 2021)
The reactive oxygen species (ROS) produced during exercise act as a double-edged sword because they may cause oxidative damage but also play a role in the signaling pathways. A supplementation of exogenous antioxidants can reduce the total amount of ROS during exercise while may also affect the ROS’ role in the signaling pathways of mitochondrial biogenesis. It has been suggested that hydrogen gas, as an antioxidant, can selectively scavenge hydroxyl radicals but does not affect superoxide anion’s signal transduction. The aim of this study was to compare the effects of one-hour hydrogen gas inhalation 30 min prior to a treadmill exercise on the key biomarkers of mitochondrial biogenesis and related signaling pathways, and the activities of endogenous antioxidant enzymes, with that of vitamin C, in rat skeletal muscle. Eighty-one 8-week-old male Sprague Dawley rats were randomly assigned to three interventions (exercise-only, exercise+4%H2, and exercise+vitamin C at 500 mg/kg weight, with 27 rats under each intervention), and sampled at pre, immediately post and 4 h post a 60-min treadmill exercise at speed of 27 m/min and flat inclination, with 9 rats in each sub-group. Expression of mitochondrial biogenetic markers and related signaling molecules in gastrocnemius muscle, and concentrations of oxidative stress markers in serum were measured. Two-way ANOVA or Kruskal-Wallis analyses showed that both hydrogen inhalation and vitamin C supplementation significantly reduced serum levels of MDA immediately after exercise and AGEs 4 h after exercise. The pre-exercise supplement of vitamin C significantly reduced mitochondrial complex Ⅳ concentrations and PGC-1α, NRF-1, TFAM gene expression levels compared to the pre-exercise group, but the hydrogen gas intervention didn’t result in a reduction in these measurements. Unlike vitamin C, hydrogen inhalation didn’t blunt post-exercise mitochondrial biogenetic signals, but resulted in an increase of complex Ⅳ concentration, activation of PGC-1α, and TFAM and NRF-2 gene transcription, and up-regulation of PGC-1α protein expression. The findings indicated that hydrogen gas inhalation could play the role as an effective antioxidant in response to the exercise, whilst didn’t significantly affect mitochondrial biogenesis. The dose-response relationship and antioxidant effects in different types of exercise for hydrogen inhalation require further investigation.